Development and Validation of the Questionnaire “Types of Role Self-Efficacy” - V.V. Enin (Социальная психология и общество)
Objective. Validation and reliability testing of a questionnaire that allows identifying types of role self-efficacy of an individual. Background. Self-efficacy of an individual, manifested in specific activities, can be a characteristic of role behavior. To date, there are no diagnostic methods that allow us to study the manifestation of role self-efficacy and its types. Study design. The study was carried out using an anonymous survey of respondents and a group of experts, which made it possible to determine the content, convergent, construct validity of the questionnaire, as well as test it for reliability by studying the internal consistency of the questionnaire scales and test-retest validity. Conducted from September to January 2023. Participants. The total sample of the study was 1720 people, among them 1333 girls (78%) and 387 boys (22%). The average age of respondents was 20,1 (SD = 1,9). When conducting a correlation study, the sample consisted of 1540 people (1200 girls and 340 boys), the gender and age composition did not change. Measurements. Self-efficacy test questionnaire authored by J. Maddux, M. Scheer, adapted by A.V. Boyarintseva. The scale of general self–efficacy, developed by R. Schwarzer, M. Jerusalem, adapted by V.G. Romek. Multidimensional questionnaire for self-attitude research (MIS – methodology for self-attitude research), created by S.R. Panteleev. E. Berne's test "Role positions in interpersonal relationships". Confirmatory factor analysis, Cronbach's alpha coefficient, and correlation analysis were used to process and analyze the data. Data analysis was performed using the R programming language (v.4.3) in the RStudio environment (v. 2023.12.1+402 "Ocean Storm"). Results. A good consistency of the three scales of the questionnaire was revealed (Cronbach's alpha > 0,8), the three-factor structure of the questionnaire GFI = 0,94, AGFI = 0,93, TLI = 0,92, SRMR = 0,03, RMSEA = 0,04 was confirmed. The construct validity of the questionnaire and retest reliability have been confirmed. Conclusions. As a result of confirmatory factor analysis, the original three-factor model of the questionnaire was confirmed. This technique allows for the first time to diagnose the types of role self-efficacy of an individual without resorting to other means of diagnosing them.